Moroccan Agro-Food Companies: Performance Evaluation through the Balanced Scorecard Method - Aicha Farissi; Mohamed EL Oumami; Zitouni Beidouri (International Journal of Supply Chain Management, 2020)
This research aimed to examine the development of the Moroccan food enterprises. It aims to identify critical issues that would contribute to the effective performance measurement function in these types of companies. This study used the qualitative research. Five case studies from various companies in the sector that engage in different activities: Flour milling company (ISO 22000); Cheese manufacturing (ISO 9001); Production of soft drinks (ISO 22000); Canned fish (ISO 9001); Coffee production (ISO 9001). The paper presents important issues: development constraints; Strategies; systems set up; performance indicators. The analysis is based on the balanced scorecard, which proposes a global dimension of the piloting with a decline on the operational level. We have classified the determinants of BSC, while using the ABC method, to measure the importance of each indicator, to answer the question: which factors have the most influence on the performance? It is assumed that the financial and accounting criteria alone are not sufficient to measure the performance of the company. This stage of performance evaluation is very important, before proposing improvement actions, or a corrective method for an effective and a permanent strategy. Keywords— Performance, constraints, Balanced Scorecard, Moroccan food companies.